Association between perfluoroalkyl and polyfluoroalkyl substances and adolescents' sleep disorders: NHANES 2005–2018 - Gao, Bocheng; Gong, Yanju; Lu, Yan; Gou, Shuhua; Lai, Xingyue; Luo, Gan; Yang, Hong (Frontiers in Nutrition, 2025)
BackgroundPrevious research indicates that per- and polyfluoroalkyl substances (PFAS) can disrupt metabolism and neurological function via endocrine pathway interference and neuroinflammation. These effects may impair melatonin secretion and disrupt circadian rhythm regulation, suggesting potential links to sleep health. However, the impact of PFAS exposure on adolescent sleep remains unclear. This study examines the associations between PFAS exposure and sleep health indicators in U.S. adolescents.MethodsData from 838 adolescents who participated in the 2005–2018 National Health and Nutrition Examination Survey (NHANES) were analyzed to investigate the association between PFAS exposure and physician-diagnosed sleep disorders. Eight PFAS compounds were identified. Multivariate logistic regression models, restricted cubic spline (RCS) curves, Bayesian kernel machine regression (BKMR), and weighted quantile sum (WQS) regression were used to assess single, linear, and combined effects on adolescent sleep disorders.ResultsNegative associations were observed between adolescent sleep disorders and three PFAS compounds, specifically perfluorooctanoic acid (PFOA), perfluorooctanesulfonic acid (PFOS), and perfluorononanoic acid (PFNA). RCS analysis revealed a significant linear relationship (P for non-linear > 0.05). The BKMR and WQS models demonstrated a combined effect of PFAS exposure on sleep disorders, with PFOS demonstrating the most substantial contribution (effect size: 0.91). The stratified analysis revealed that PFOS exposure had a greater impact on females [odds ratio (OR): 0.54, 95% confidence interval (CI): 0.33–0.87] than males (OR: 0.50, 95% CI: 0.24–1.01), suggesting sex-specific differences in vulnerability.ConclusionsOur findings indicate a negative correlation between specific PFAS and specific sleep disorders in adolescents, with PFOS being the dominant effect component in the PFAS mixture and stronger effects observed in females. However, due to the cross-sectional nature of the study, a causal relationship cannot be established. These results highlight the potential public health impact of PFAS exposure and the need to further investigate the underlying mechanisms and causal pathways in future longitudinal or experimental studies.